The Determination of Graph Isomorphism Using R Software - He, Chaobing (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2020)
This paper considers the determination of graph isomorphism using R. After the preliminaries about graph theory is introduced systematically, the graph isomorphism determination process are studied. Then computer program for the determination of graph isomorphism is written using R. According to these R codes, the paper determines the isomorphism of three 3-regular graphs on 6 vertices and three 3-regular graphs on 8 vertices respectively, and the output proves that the R codes are very practical and effective.